Existence of Solutions for Fractional Differential Equations Involving Two Riemann-Liouville Fractional Orders (Analysis in Theory and Applications, 2018)
In this work, we study existence and uniqueness of solutions for multi-pointboundary value problem of nonlinear fractional differential equations with two fractionalderivatives. By using the variety of fixed point theorems, such as Banach\u2019s fixedpoint theorem, Leray-Schauder\u2019s nonlinear alternative and Leray-Schauder\u2019s degreetheory, the existence of solutions is obtained. At the end, some illustrative examplesare discussed.
Keywords: Riemann-Liouville integral; existence; fixed point theorem; Leray-Schauder alternative.